Civil Disobedience, Costly Signals, and Leveraging Injustice - Ten-Herng Lai (Ergo, An Open Access Journal of Philosophy)
Civil disobedience, despite its illegal nature, can sometimes be justified vis-à-vis the duty to obey the law, and, arguably, is thereby not liable to legal punishment. However, adhering to the demands of justice and refraining from punishing justified civil disobedience may lead to a highly problematic theoretical consequence: the debilitation of civil disobedience. This is because, according to the novel analysis I propose, civil disobedience primarily functions as a costly social signal. It is effective by being reliable, reliable by being costly, and costly primarily by being punished. My analysis will highlight a distinctive feature of civil disobedience: civil disobedients leverage the punitive injustice they suffer to amplify their communicative force. This will lead to two paradoxical implications. First, the instability of the moral status of both civil disobedience and its punishment to the extent where the state may be left with no permissible course of action with regard to punishing civil disobedience. Second, by refraining from punishing justified civil disobedience, the state may render uncivil disobedience—illegal political activities that fall short of the standards of civil disobedience—potentially permissible.Click the links below to download an audio version of this article's content:Full article (with endnotes read after the main text)Full article (with footnotes read as they appear in the main text)